Proton-Binding Motifs of Membrane-Bound Proteins: From Bacteriorhodopsin to Spike Protein S - Bondar, Ana-Nicoleta (Frontiers in Chemistry, 2021)
Membrane-bound proteins that change protonation during function use specific protein groups to bind and transfer protons. Knowledge of the identity of the proton-binding groups is of paramount importance to decipher the reaction mechanism of the protein, and protonation states of prominent are studied extensively using experimental and computational approaches. Analyses of model transporters and receptors from different organisms, and with widely different biological functions, indicate common structure-sequence motifs at internal proton-binding sites. Proton-binding dynamic hydrogen-bond networks that are exposed to the bulk might provide alternative proton-binding sites and proton-binding pathways. In this perspective article I discuss protonation coupling and proton binding at internal and external carboxylate sites of proteins that use proton transfer for function. An inter-helical carboxylate-hydroxyl hydrogen-bond motif is present at functionally important sites of membrane proteins from archaea to the brain. External carboxylate-containing H-bond clusters are observed at putative proton-binding sites of protonation-coupled model proteins, raising the question of similar functionality in spike protein S.